ENCOURANGING WRITING SKILL USED ENGLISH DIARY WRITING - Zahro, Khalifatus; Endah Nur Tjendani; Imam Ghozali (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
ABSTRACTThis study aims to implement an English diary to encouraging the improvement of students' writing skills. This study was conducted using quantitative methods with quasi-experimental design. The study population consisted of 15 students from the experimental and control classes. The classes were then randomly assigned to the experimental and control classes. The experimental class was taught by applying diary writing, while the control class was taught by applying conventional teaching techniques or without applying diary writing. The study was further conducted by following the procedure: giving a pre-test, implementing the intervention, and giving a posttest. Data were collected through tests and interviews. The test data were then calculated using t-test on SPSS 21 with sig. 5% and the interview data was described. The t-test was conducted by calculating the posttest and the scores obtained in both classes showed that the t value on the posttest (2.094) and the acquisition score (2.703) was higher than the t table (1.667) with df = 70 at the 0.05 significance level. So, the t-test result > t-table which means H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. In addition, this finding is also in line with the interview results which show that diary writing is effective, especially in helping students find writing ideas, improve writing fluency, and develop their writing.Key word; Diary Writing, Writing Skill